Amitriptyline Sequestration by Unmodified and Modified Microcrystalline Cellulose: A Potential Treatment for Drug Overdosing - Chakraborty, Soma (Archīum Ateneo, 2023)
Microcrystalline cellulose (MCC) was studied as a sequestrant of amitriptyline from its aqueous solution. Microcrystalline cellulose could adsorb 74% amitriptyline from pH 7.4 buffer solution in 2 h at room temperature. It was observed that the amount of amitriptyline as well as the equilibration time between MCC and amitriptyline have impact on sequestration. The amount of amitriptyline sequestered increased when the concentration of amitriptyline was increased in its aqueous solution. It also enhanced when the equilibration time between the drug and MCC increased from 5 min to 30 min, further extension of equilibration time led to less sequestration. Sequestration efficacy enhanced when MCC was modified with κ-carrageenan and when MCC was reduced to nanocrystalline cellulose (NCC). Microcrystalline cellulose in crosslinked form manifested lower sequestration efficiency than the uncrosslinked form for shorter equilibration time. This trend reversed when the equilibrium time between the sequestrant and drug was extended to 6 h. Among all the sequestrants, κ-carrageenan modified MCC particles demonstrated maximum sequestration efficiency.